Analisis Laporan Keuangan dengan Model Z-Score sebagai Alat dalam Memprediksi Bankcruptcy (Studi Kasus pada PT. Ramayana Lestari Sentosa Tbk, PT. Matahari Putra Prima Tbk, dan PT. Mitra Adiperkasa Tbk) - Rahmatullah, Muhammad; Sunarya, Erry; Jhoansyah, Dicky (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This study aims to determine the modified Altman z-score model can predict the possibility of bankcruptcy at PT. Ramayana Lestari Sentosa Tbk, PT. Matahari Putra Prima Tbk and PT. Mitra Adiperkasa Tbk, which is incorporated into Aprindo (Indonesian Retail Entrepreneurs Association), which is experiencing shifting consumption patterns. This study uses a quantitative approach descriptive analysis technique that is used to systematically describe bankcruptcy predictions after calculating using number that are entered into the Altman modification z-score formula. The result of the study show that theoretically there are 1 company in the bankcruptcy category and 2 companies in the non-bankcruptcy category. For companies that are already in a non-bankcruptcy category can maintan an existing management system, for comapnies that are in the bankcruptcy category, management must immediately make the right subscription if they dont want the company to experience bankcruptcy